The University of Florida’s Scientific Thinking and Educational Partnership Program: An Approach for Genetics Outreach - Lisa Hightower; Ricky Telg; Courtney Meyers; Tracy Irani; Maria Gallo; Brian Myers (Journal of Applied Communications, 2008)
In an effort to compete for multimillion-dollar grants that require researchers to translate their findings for the general public in the form of outreach programs, the University of Florida developed the Scientific Thinking and Educational Partnership (STEP) program. This article describes the evolution of the STEP program, from the creation of a model outreach program called ufgenetics.com—a Web site geared toward media professionals and middle school and high school teachers—to the testing, evaluation, and promotion of that project. The STEP program has garnered over $1 million in grants in just 2 years of existence.
Keywords: multimillion-dollar grants; Genetics Outreach; research; universities; programs; National Science Foundation (NSF); Educational Partnership Program